2016
DOI: 10.1097/olq.0000000000000501
|View full text |Cite
|
Sign up to set email alerts
|

Multitype Infections With Human Papillomavirus: Impact of Human Immunodeficiency Virus Coinfection

Abstract: Background Human immunodeficiency virus (HIV) infection predisposes women to genital coinfection with human papillomaviruses. Concurrent infection with multiple HPV types has been documented, but its frequency, correlates, and impact on development of precancer are poorly defined in HIV seropositive women. Methods HIV seropositive women and seronegative comparison women were enrolled in a cohort study and followed every six months 1994–2006. Cervicovaginal lavage samples were tested for HPV types using polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…We did not find as high rates of multiple HPV infection in WLWH with CIN3 as have been seen in earlier studies (32)(33)(34). One explanation may be that our study was based on biopsies rather than cell samples, and testing for HPV from biopsies is known to reduce the prevalence of multiple infections (8,9,27,35).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…We did not find as high rates of multiple HPV infection in WLWH with CIN3 as have been seen in earlier studies (32)(33)(34). One explanation may be that our study was based on biopsies rather than cell samples, and testing for HPV from biopsies is known to reduce the prevalence of multiple infections (8,9,27,35).…”
Section: Discussioncontrasting
confidence: 55%
“…The clinical importance of multiple infections is unclear as prospective evidence on this issue is limited (36). A U.S. study with long-term follow-up did not find multiple HPV infection associated with an increase of CIN3, adenocarcinoma in situ or ICC (34). In another study, including only HIVnegative women, coinfection with both low-and high-risk HPV was even associated with a reduced risk of future invasive disease and slower progression to ICC (37).…”
Section: Discussionmentioning
confidence: 99%
“…First, as patients with HIV have gained access to improved medical management and longer life spans, the incidence of HIV-associated malignancies has increased [38, 42-46]. Furthermore, studies have found higher frequencies of coinfection with multiple strains of HPV in HIV-infected patients at oral and anogenital sites, compared to those without HIV [53-56]. As some lineages and sub-lineages of HPV display biological characteristics associated with persistent infections and evolution to cancer development, patients with HIV with a high HPV strain diversity may increase the risk of carcinogenesis [53-56].…”
Section: Hiv-hpv Coinfection In Patients With Anal Squamous Intraepithelial Lesions and Anal Sccmentioning
confidence: 99%
“…Immunological mechanisms can also determine multiple infection prevalence. The prevalence of mixed infections among immunosuppressed women infected with HIV is still high (Massad et al, 2016). Women with HPV Co-infection between the ages of 30 to 40 account for only 11,32%.…”
Section: Discussionmentioning
confidence: 99%